An Optimization Model for Reducing Pumping Costs in Water Distribution Systems - Abbasali Rezapour (مجله مدل سازی در مهندسی)
The architecture of water distribution networks is inherently intricate, encompassing the strategic management of pumping mechanisms, modulation of reservoir water levels, and ensuring the delivery of water to consumers with adequate flow and pressure. A pivotal element of operating these systems is the strategic planning of pump schedules, which exerts a considerable influence on the operational expenditures. The present study introduces an optimization framework designed to schedule pump operations with the objective of minimizing energy consumption. This framework is equipped with the capability to regulate the frequency of pump activation and deactivation cycles, employing the operational durations of the pumps as binary variables and the volumetric flow rates within each conduit as continuous variables throughout the scheduling horizon. The development of this framework commenced with the formulation of the issue as a mixed nonlinear programming problem, which subsequently underwent transformation into a mixed linear programming model through the application of linearization methodologies. An empirical case study was conducted to assess the efficacy of the proposed model. The examination of the results indicates that the use of the proposed optimization method leads to a reduction in energy costs by approximately 16 percent and an increase in the efficiency of the water distribution system.